Comparative Characterization of the TiN and TiAlN Coatings Deposited on a New WC-Co Tool Using a CAE-PVD Technique - Alecs Andrei Matei; Ramona Nicoleta Turcu; Ion Pencea; Eugen Herghelegiu; Mircea Ionut Petrescu; Florentina Niculescu (Crystals, 2023)
The main objective of this work was to assess and compare the structure and mechanical properties of the TiN and TiAlN coatings deposited on a new WC-Co tool using the cathodic arc evaporation vacuum deposition (CAE-PVD) technique. The cutting tool was sintered at high temperature and high pressure using a powder tungsten carbide matrix ligated with cobalt (WC-Co). Powdered grain growth inhibitors (TiC, TaC, and NbC) were admixed into the matrix to enhance its strength and to facilitate the adhesion of the Ti base coatings. Detailed scanning electron microscopy with energy-dispersive spectrometry (SEM-EDS) and X-ray diffraction (XRD) analyses were performed, aiming to substantiate the effectiveness of the inhibitor additions. XRD data were thoroughly exploited to estimate the phase contents, average crystallite sizes (D), coating thicknesses (t), texture coefficients (Thkl), and residual stress levels (σ). Atomic force microscopy (AFM) was used to calculate the average roughness (Ra) and the root mean square (Rq). The microhardness (µHV) was measured using the Vickers method. The TiAlN characteristics (D = 55 nm, t = 3.6 μm, T200 = 1.55, µHV = 3187; σ = −2.8 GPa, Ra = 209 nm, Rq = 268 nm) compared to TiN ones (D = 66 nm, t = 4.3 μm, T111 = 1.52, µHV = 2174; σ = +2.2 GPa, Ra = 246 nm, Rq = 309 nm) substantiate the better adequacy of the TiAlN coating for the WC-Co substrate. The structural features and data on the TiN and TiAlN coatings, the tool type, the different stress kinds exerted into these coatings, and the way of discrimination of the coating adequacy are the novelties addressed in the paper.